Hidden blood loss in adolescent idiopathic scoliosis patients undergoing posterior spinal fusion surgery: a retrospective study of 765 cases at a single centre - Lipeng Wang; Jiangli Liu; Xiaoxiao Song; Muhui Luo; Yongquan Chen (BMC Musculoskeletal Disorders, 2021)
Abstract Background In scoliosis corrective surgery, total blood loss is composed of visible blood loss, including intraoperative haemorrhage and drainage, and hidden blood loss in which blood extravasates into the tissues and accumulates in the surgical field. The purpose of this study was to investigate hidden blood loss (HBL) and its potential risk factors in adolescent idiopathic scoliosis patients undergoing posterior spinal fusion surgery and elucidate the influence of HBL on the necessity for postoperative blood transfusion. Methods We retrospectively studied adolescent idiopathic scoliosis patients undergoing posterior spine fusion for adolescent idiopathic scoliosis from January 2014 to December 2018 at our hospital. The patients’ demographics, blood loss-related parameters, surgeries and blood loss data were extracted. The association between patient characteristics and HBL was analyzed by Pearson or Spearman correlation analyses. Multivariate linear regression analysis was used to determine independent risk factors associated with HBL. Binary logistic regression analysis was used to analyze the influence of HBL on the necessity for postoperative blood transfusion. Results A total of 765 patients, of whom 128 were male and 637 were female (age range 10–18 years), were included in this study. The mean volume of HBL was 693.5 ± 473.4 ml, accounting for 53.9 % of the total blood loss. The multivariate linear regression analysis revealed that preoperative Hct (p = 0.003) and allogeneic blood transfusion (p < 0.001) were independent risk factors for HBL, while tranexamic acid (p = 0.003) was negatively correlated with HBL. Binary logistic regression analysis showed that HBL > 850 ml (P < 0.001, OR: 8.845, 95 % CI: 5.806–13.290) was an independent risk factor for the necessity for postoperative blood transfusion. Conclusions Substantial HBL occurred in adolescent idiopathic scoliosis patients undergoing posterior spinal fusion surgeries. Allogeneic blood transfusion and preoperative Hct were independent risk factors for HBL, while tranexamic acid was negatively related to HBL. HBL and its influencing factors should be considered when planning perioperative transfusion management. Patients with HBL greater than 850 ml should be closely monitored in cases of postoperative anaemia. Level of evidence Level III.